A potent anti-inflammatory peptide from the salivary glands of horsefly. Issue 1 (December 2015) - Wei, Lin; Huang, Chunjing; Yang, Hailong; Li, Min; Yang, Juanjuan; Qiao, Xue; Mu, Lixian; Xiong, Fei; Wu, Jing; Xu, Wei
Abstract Background A diverse group of physiologically active peptides/proteins are present in the salivary glands of horseflyTabanus yao (Diptera, Tabanidae) that facilitate acquisition of blood meal. However, their roles in the regulation of local inflammation remains poorly understood. Methods Induction expression profiles of immune-related molecules in the salivary glands ofT. yao was analyzed by quantitative PCR (qPCR) after bacterial feeding. A significantly up-regulated molecule (cecropin-TY1) was selected for anti-inflammatory assay in lipopolysaccharide (LPS)-stimulated mouse peritoneal macrophages. The transcription levels of inducible NO synthase (iNOS) and pro-inflammatory cytokines were quantified by qPCR. Nitric oxide (NO) production was determined by Griess reagent. Pro-inflammatory cytokine production was determined by an enzyme-linked immunosorbent assay (ELISA). The inflammatory signals were assayed by Western blotting analysis. The secondary structure of cecropin-TY1 was measured by Circular dichroism (CD) spectroscopy. Interaction of cecropin-TY1 with LPS was evaluated by the dissociation of fluorescein isothiocyanate (FITC)-conjugated LPS aggregates and neutralization of LPS determined by a quantitative Chromogenic End-point Tachypleus amebocyte lysate (TAL) assay kit. Homology modeled structure analysis and mutation of key residues/structures were performed to understand its structure-activity relationship. Results Cecropin-TY1 was demonstrated to possess high anti-inflammatory activity and low cytotoxicity toward mouse macrophages. In LPS-stimulated mouse peritoneal macrophage, addition of cecropin-TY1 significantly inhibited the production of nitric oxide (NO) and pro-inflammatory cytokines. Further study revealed that cecropin-TY1 inhibited inflammatory cytokine production by blocking activation of mitogen-activated protein kinases (MAPKs) and transcriptional nuclear factor-κB (NF-κB) signals. Cecropin-TY1 even interacted with LPS and neutralized LPS. The secondary structure analysis revealed that cecropin-TY1 adopted unordered structures in hydrophobic environment but converted to α-helical confirmation in membrane mimetic environments. Homology modeled structure analysis demonstrated that cecropin-TY1 adopted two α-helices (Leu3-Thr24, Ile27-Leu38) linked by a hinge (Leu25-Pro26) and the structure surface was partly positively charged. Structure-activity relationship analysis indicated that several key residues/structures are crucial for its anti-inflammatory activity including α-helices, aromatic residue Trp2, positively charged residues Lys and Arg, hinge residue Pro26 and N-terminal amidation. Conclusions We found a novel anti-inflammatory function of horsefly-derived cecropin-TY1 peptide, laying groundwork for better understanding the ectoparasite-host interaction of horsefly with host and highlighting its potency in anti-inflammatory therapy for sepsis and endotoxin shock caused by Gram-negative bacterial infections.